Pengaruh Profitability, Firm Size, Leverage, Dan Managerial Ownership Terhadap Earning Management - Daniel Steven, Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to test empirically the effect of profitability, firm size, leverage, and managerial ownership in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. Company data used in this study were 37 manufacturing companies that have been selected through the purposive sampling techniques. Research data processing uses multiple regression analysis helped by Eviews 10 and Microsoft Excel 2016. The results shows that independent variables simultaneously have a significant effect on earning management. The results show that profitability has a positive and significant effect on earning management, while firm size, leverage, and managerial ownership have no significant effect on earning management. The implication of this research shows the importance of earning management behavior to produce financial statement that can fulfilled the expectations of the stakeholders.